The Relationship of Islamic Animation Content to Islamic Religious Education of Students at SD Negeri 004 West Balikpapan - Syahida Salwa; Humaidy Humaidy (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2026)
The background of this study is based on the rapid development of technology and information, and students having a strong moral foundation. Islamic Religious Education (IRE) packaged through educational entertainment such as Islamic animated series is considered capable of attracting students' interest and instilling moral values in a fun way. This study aims to determine the use of Islamic animation content, the implementation of Islamic Religious Education (PAI), and the relationship between the two in PAI subjects at SD Negeri 004 Balikpapan Barat.  This study is based on Arsyad's theory, which states that audiovisual media such as animation can increase students' attention and understanding of learning. This is supported by Piaget's theory of child development, which states that elementary school students find it easier to understand information through visuals and concrete stories. Meanwhile, according to Zakiah Daradjat in Ashari et al., Islamic Religious Education is a planned process to shape pious individuals who are able to practice Islamic teachings in their daily lives. The research method used was quantitative with data collection through observation, interviews, and questionnaires. The research population consisted of 77 students with a sample of 40 respondents selected using simple random sampling. Data analysis was performed using the Spearman Rank Correlation formula with the help of IBM SPSS Statistics Version 27. The results of the study showed a significance value (Sig. 2-tailed) of 0.001 < 0.01, a calculated r value of 0.506 > r table (0.312), which means that there is a positive relationship with a moderate correlation between the use of Islamic animation content and the implementation of PAI. Thus, H₀ is rejected and Hₐ is accepted, so it can be concluded that there is a relationship between Islamic animation content and Islamic Religious Education for students at SD Negeri 004 Balikpapan Barat. The use of Islamic animation content has a positive impact on improving the quality of learning, religious attitudes, and student interest in learning, although its effectiveness still needs to be optimized in terms of cognitive, psychomotor, and activity in religious activities.